PERAN GURU MADRASAH TSANAWIYAH NEGERI 1 PIDIE JAYA TERHADAP KUALITAS PRESTASI SISWA - Muhammad Zaki; Wahdini; Muna Irtiyah; Saifuddin (Indonesian Journal of Islamic and Social Science, 2026)
This study examines the role of teachers at Madrasah Tsanawiyah Negeri 1 (MTsN 1) Pidie Jaya in relation to the quality of student achievement. Teachers are the most determining component in the overall educational system. Their roles encompass not only delivering subject matter but also acting as educators, counselors, motivators, facilitators, and evaluators. This study employs a descriptive qualitative approach with data collection techniques including observation, in-depth interviews, and documentation. Research subjects consist of the principal, teachers, and students of MTsN 1 Pidie Jaya. The results indicate that teachers' roles at MTsN 1 Pidie Jaya significantly contribute to improving the quality of student achievement in both academic and non-academic fields. Supporting factors include teachers' pedagogical competence, classroom management skills, motivation provision, and active involvement in extracurricular activities. This research is expected to serve as a reference in efforts to improve the quality of education in madrasah.